Monitoring Therapeutical Intervention with Ezetimibe Using Targeted Near-Infrared Fluorescence Imaging in Experimental Atherosclerosis - Kristof Graf; Thore Dietrich; Michael Tachezy; Frank-Detlef Scholle; Kai Licha; Philipp Stawowy; Michael Grafe; Peter Hauff; Eckart Fleck (Molecular Imaging)
Ezetimibe (EZE), an inhibitor of cholesterol absorption, reduces atherosclerosis in apolipoprotein E–deficient (apo –/– ) mice. The matrix protein ED-B fibronectin (ED-B) is upregulated in atherosclerotic lesions. Using a novel conjugate for near-infrared fluorescence (NIRF) imaging targeting ED-B, we studied the effect of EZE on plaque lesion formation in apoE –/– mice. ApoE –/– mice received EZE (5 μg/kg/d) or chow up to the age of 4, 6, and 8 months. NIRF imaging of aortic lesions was performed 24 hours after intravenous application ex vivo and in vivo. Plaque lesion formation was analyzed by histology and immunohistochemistry. Aortic lesion formation detected by Sudan staining and NIRF imaging was significantly reduced at 6 and 8 months ( p < .001). Plaque areas determined by NIRF imaging significantly correlated with Sudan staining ( p < .001). EZE treatment resulted in a significant reduction in plaque macrophage and ED-B immunoreactivity (both p < .05) in brachiocephalic lesions. There was a significant reduction in plaque size in brachiocephalic arteries in 8-month-old mice treated with EZE compared with mice during short-term treatment ( p < .05), indicating EZE plaque regression. Targeted NIRF imaging showed a correlation to histologic lesion extension during therapeutical intervention in experimental atherosclerosis.